Ambient water quality criteria derived using probabilistic risk assessment. (4th October 2022) - Barnhart, Brad; Flinders, Camille; Johnson, Giffe; Wiegand, Paul; Anderson, Paul; Morrison, Emily; Houck, Gina
Abstract: National recommendations for numeric human health ambient water quality criteria (AWQC) for toxic substances are derived by the US Environmental Protection Agency (USEPA) using a deterministic approach that combines point estimates for exposure, toxicity, and acceptable risk. In accordance with the Clean Water Act, states, territories, and authorized tribes must either adopt these recommendations or modify and replace them with criteria using an alternative, scientifically defensible method. Recent reports have criticized the deterministic approach, stating that it suffers from compounded conservatism by selecting upper percentiles or maximum values for multiple inputs and that it cannot directly determine what portion of the population a given criterion protects. As an alternative, probabilistic risk assessment (PRA) has been promoted as a more transparent and robust method for deriving AWQC. Probabilistic risk assessment offers several advantages over the deterministic approach. For example, PRA uses entire data distributions rather than upper‐percentile point estimates to specify exposures, thereby reducing compounded conservatism. Additionally, because it links acceptable risk targets with specific segments of the exposed population, PRA‐based AWQC demonstrably protects multiple subsets of the population. To date, no study has quantitatively compared deterministic and PRA approaches and resulting AWQC using national inputs consistent with USEPA guidance. This study introduces a PRA method for deriving AWQC and presents case studies to compare probabilistically derived AWQC with USEPA's 2015 recommendations. The methods and results of this work will help federal and state regulators, water quality managers, and stakeholders better understand available approaches to deriving AWQC and provide context to assumption‐ and method‐specific differences between criteria. Integr Environ Assess Manag 2023;19:501–512. © 2022 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC). Key Points: Probabilistic risk assessment is used to derive numeric human health ambient water quality criteria. Probabilistic risk assessment is compared with the traditionally used deterministic approach using national inputs consistent with guidance from the USEPA. Probabilistic risk assessment offers several advantages over the deterministic approach. Probabilistic risk assessment uses entire data distributions rather than upper‐percentile point estimates to specify exposures and demonstrably protects multiple subsets of the population by linking acceptable risk targets with specific segments of the exposed population.